Minimum Wages and Spatial Equilibrium: Theory and Evidence - Joan Monras (Institute for the Study of Labor (IZA), 2015)
Often, minimum wage laws are decided at the state or regional level, and even when not, federal level increases are only binding in certain states. This has been used in previous literature to evaluate the effects of minimum wages on earnings and employment levels. This paper introduces a spatial equilibrium model to think about the seemingly conflicting findings of this previous literature. The model shows that the introduction of minimum wages can lead to an increase or a decrease in population depending on the local labor demand elasticity and on how unemployment benefits are financed. The paper provides empirical evidence consistent with the model. On average, increases in minimum wages lead to increases in average wages and decreases in employment. The low-skilled local labor demand elasticity is estimated to be above 1, which in the model is a necessary condition for the migration responses found in the data. Low-skilled workers, who are presumably the target of the policy, tend to leave or avoid moving to the regions that increase minimum wages.
Keywords: J38; 330; minimum wages; spatial equilibrium; internal migration